Determination of Purchase Decisions through Purchase Interest: Analysis of Somethinc Skincare Product Prices - Aprelyani, Siska (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This article discusses the influence of price through Purchase Decisions on Purchase Intention. This research is a quantitative research where the objects used are Generation Z in Bekasi City. The number of samples used in this study was 200 respondents. The design used is hypothesis testing using the structural equitation model (SEM) method - SmartPLS 4.0. Based on the conceptual framework created, it can be concluded that the hypothesis is that price influences purchase interest and purchase decisions.